Findings from the Global Youth Tobacco Survey (GYTS) in Czech Republic, Hungary, Poland and Slovakia--smoking initiation, prevalence of tobacco use and cessation - Baska, Tibor; Sovinová, Hana; Nemeth, Agnes; Przewozniak, Krysztof; Warren, Charles W; Kavcová, Elena (Sozial- und Präventivmedizin, 2006)
OBJECTIVES: To show selected findings from the Global Youth Tobacco Survey (GYTS) conducted in Czech Republic, Hungary, Poland and Slovakia. METHODS: Representative sample of 16918 school children aged 13-15 years; data were obtained through uniform questionnaires. The fieldwork was conducted in 2002 and 2003. RESULTS: Age at initiation of smoking was particularly earlier in Czech Republic, Poland, and Slovakia than in Hungary. Over one third of the students reported current cigarette smoking in Czech Republic (34.9%) and Hungary (33.5%) compared to about one-fourth in Slovakia (24.3%) and Poland (23.3%). Among current smokers, about two thirds in Slovakia (64.0%) desired to stop smoking, while only one third in Hungary (36.7%). The prevalence of current cigarette smoking was similar between genders. DISCUSSION: Smoking prevalence in these countries is considerably higher than worldwide data. Women's smoking could be an important public health problem in the future. Repeated surveys could show trends and give a clearer picture of the epidemiological situation.
Keywords: Female; Smoking Prevention; prevence kouření; průzkumy a dotazníky; Hungary; věkové faktory; Adolescent; mužské pohlaví; Smoking; odvykání kouření; Humans; Prevalence; kouření; Adolescent Behavior; Sex Factors; Czech Republic; chování mladistvých; Slovakia; lidé; Maďarsko; Surveys and Questionnaires; sexuální faktory; Age Factors; ženské pohlaví; Česká republika; Poland; prevalence; sběr dat; Polsko; Data Collection; Smoking Cessation; Male; mladiství; Slovenská republika